Residue 39 of Kir6.2 drives a difference in ATP sensitivity in human and canine beta-cell KATP channels - Vedovato, Natascia; Ashcroft, Frances M.; Catchpole, Brian; Davison, Lucy J. (Frontiers in Physiology, 2025)
ATP-sensitive potassium (KATP) channels link beta-cell metabolism to electrical activity. By modulating the beta-cell membrane potential, they finely regulate glucose-stimulated insulin secretion. KATP channels are hetero-octameric complexes composed of four pore-forming subunits (Kir6.2, encoded by KCNJ11) and four regulatory subunits (SUR1, encoded by ABCC8). A multi-species alignment of the KCNJ11 gene revealed that, although the sequence is highly conserved, residue 39 varies among different mammals. Previous studies have shown that this residue plays a critical role in regulating KATP channel activity and its mutation results in neonatal diabetes in humans. We therefore explored whether the canine and human KATP channel show different ATP sensitivities as a result of their sequence variation. We used patch-clamp electrophysiology to investigate species variation in the ATP sensitivity of the KATP channel. Functional studies showed that canine KATP channels exhibit reduced ATP sensitivity compared to human channels. However, stimulation by MgADP was unaffected. We next compared the ATP sensitivity of hybrid channels (human Kir6.2 with canine SUR1, and vice versa), as well as KATP channels in which residue 39 was swapped between human and canine Kir6.2. In each case, ATP sensitivity was mainly determined by the identity of the residue at position 39. Our study suggests that the ATP sensitivity of the pancreatic KATP channel differs between human and dog. This suggests that the beta-cell membrane potential and potentially insulin release may be fine-tuned differently across species.